Much More Than an ›Extra‹—Writing as a »Chief Character« in Film and Video (KULT_online, 2011)
Christine Stenzer's doctoral thesis is the first historical and systematic survey of writing as a 'chief character' in film and video and closes an academic void. The subject-matter of her study consists of "irregular, irritating and innovative" integrations of writing beyond its conventional use in narrative fiction as is the case for credits, subtitles and intertitles. Her broad subject of investigation contains silent and avant-garde movies, animated movies, experimental movies, video art, advertising films and music videos, title sequences and trailers. Owing to the abundance of material, she is able to draw up a large 'forms-and-functions catalogue,' wherein she points out as a main function the reflection of the materiality and the mediality of writing and film as well as their perception by the recipient.